Molecular dynamics study on the thermal conductivity of bilayer graphene with nitrogen doping. (March 2020) - Zhang, Xingli; Zhang, Jianlan; Yang, Ming
Abstract: By using non-equilibrium molecular dynamics simulations, we investigated the impacts from nitrogen doping on the thermal conductivity of bilayer graphene. The results show thermal conductivity of nitrogen-doped bilayer graphene in plane directions are significantly reduced with the increase of nitrogen doping concentration. However, the variation of thermal conductivity with changes in temperature is less significant compare with that of perfect bilayer graphene. In addition, the thermal conductivity of nitrogen-doped bilayer graphene shows nonlinear trend when changing the nitrogen impurity location. The underlying physical mechanism of the simulation results are analyzed from phonon spectrum and phonon relaxation time perspectives, suggesting that phonon scatterings and phonon modes mismatches are the main sources of our simulation results. Based on these investigations, an effective guidance to the applications of nitrogen-doped bilayer graphene in nanosacle electronic devices is proposed. Highlights: The impacts from nitrogen doping on the thermal transport of bilayer graphene and the physical mechanism are investigated. The phonon density of states and phonon relaxation time are analyzed to understand the underlying physical mechanism of the simulation results. Bilayer graphene doping with nitrogen is an effective method to realize thermal management in nanoelectronic devices.